Comparative study on fixation of Jones fracture using cannulated screws vs tension band - Ali Ahmed Ali Younes; Tharwat Mohmed Abd Elrahman; Mohamed Ramadan Elfeshawy; Yaser Elsayed Hassan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background; Currently, there is still debate on how to treat fifth metatarsal jones fractures, particularly those in area II. Aim and objectives; study aims to evaluate the relative efficacy of tension band vs cannulated screw surgery for fixing fractures of the fifth metatarsal base (Jones fracture).Patients and methods; Patients with traumatic base fifth metatarsal bone fractures who were admitted to the emergency rooms of the Alzahraa University Hospital and the Sohag General Hospital were the focus of this prospective thesis study. Their follow-up was scheduled to last for four months and would take place in the outpatient clinics of the Alzahraa Orthopedic Center and the Sohag General Hospital between April 2021 and the end of November 2021.Result; The two groups differed significantly from one another. Assessment of post-operative discomfort at two weeks, six weeks, and twelve weeks (3 months). Every patient was asked to assess his or her level of pain on a scale from 0 to 10, following the most widely used numeric rating scale. Conclusion; A safe and efficient approach for treating an acute Jones fracture at the base of the fifth metatarsal is early screw fixation or tension banding. The early surgical intervention leads to an earlier clinical union and enables patients to resume their regular daily activities more quickly than cast therapy, which has a significant nonunion rate.